(untitled) (Journal of Philosophy Culture and Political Science, 2024)
In modern conditions, digital platforms act as arenas for the formation of collective goals and identity, being the main means of interaction with a diverse audience. The increasing political competition and the need to attract the attention of voters force political parties to skillfully use all communication channels. Within the framework of global informatization, this article examines the transformative impact of modern information and communication technologies on the political arena. It explores the evolving dynamics of the formation of the image of political figures in the online sphere. In the context of rapid technological progress, the study highlights the urgent need to study political and governmental structures of interaction with social networks, and identify tactics to influence a wide audience. Emphasizing the strategic imperative, the study advocates the skillful formation and promotion of one’s image using the prevailing capabilities of relevant technologies and information channels, especially in the field of the Internet. The research focuses on scrutinizing the methods and algorithms employed by political parties in Kazakhstan on social networks, aiming to identify the most active and widespread approaches. The study’s significance lies in its potential to offer insights into diverse methods utilized by online media for promoting cultural and economic activities. By elucidating the intricate relationship between social media algorithms and the digital portrayal of political parties, this research provides valuable information essential for a comprehensive grasp of modern political communication in the digital age. Keywords: Social media, Audience, Political parties, Globalization, Algorithms, Digital perception, Influence, Information technologies, Communication